Tracking Control using Sensor Technology Solar Cell: In Real Time Domain Analysis (London Journal of Engineering Research, 2024)
Solar Tracking (ST) is employed to maximize output power due to the nonlinear characteristics of renewable energy sources. Sunlight is considered the most reliable traditional source of energy when energy emergencies arise. First, we present some basic characteristics of the motor in the form of Tables and Figures. Solar panel tracking is, therefore, necessary to enhance their efficiency. In this article, we present the sensor based viz. STM32 microcontroller has been implemented in real-time using the PV arrays. In addition, we did an analysis of stateof-the-art reviews of solar photo-voltaic systems for this research article. Researchers have developed sensor-based techniques to improve renewable energy systems. This technique performs better than other traditional methods.
Keywords: Loess Plateau; Ancient landslide; Unloading creep; Differential deformation; Stress path; Solar Panel; Tracking Control; Sensor Technology.